Prescriptions and conceptions of school equality in the development of summative assessments - Luisoni, Marc; Monnard, Isabelle (Swiss Journal of Educational Research, 2020)
This study examines the influence of various prescriptions on the development of summative evaluation tools and the links with school concepts of justice. The methodological approach chosen is based on a quantitative perspective and uses two scales of measurement that make it possible to identify evaluator profiles in relation to prescriptions and principles of justice. Teachers from all the obligatory schooling in the canton of Fribourg in Switzerland are the subjects of this study. The results show specificities between the different levels of primary school and the obligatory secondary school in terms of the influence of prescription and conceptions of justice in the school.